2017
DOI: 10.1111/jog.13325
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of endometriosis on partners

Abstract: Overall, our findings suggest that endometriosis can have a significant impact on partners with respect to day-to-day living, finances, sex lives, and relationships. Improvements can be made to engage partners in the treatment process, and to provide better education, support, and holistic management to women and families who suffer with endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
2
27
0
2
Order By: Relevance
“…Some participants in the study were complaining about the lack of support from the spouse and the controversy and disagreement with him due to the illness. The results of other studies are also consistent with the present study (Ameratunga et al., 2017). One of the most important threats to the emotional intimacy of couples is sexual problems.…”
Section: Discussionsupporting
confidence: 94%
“…Some participants in the study were complaining about the lack of support from the spouse and the controversy and disagreement with him due to the illness. The results of other studies are also consistent with the present study (Ameratunga et al., 2017). One of the most important threats to the emotional intimacy of couples is sexual problems.…”
Section: Discussionsupporting
confidence: 94%
“…We identified 13 studies in women with endometriosis that address the impact of endometriosis on the personal relationships component of the life course. 34,45,62,[70][71][72][73][74][75][76][77][78][79] The category of "personal relationships" is inclusive of social and family connections as well as intimate partner relationships. Endometriosis may interfere with all types of interpersonal relationships, 34,62 but it is sexual health that has garnered the most research interest.…”
Section: Personal Relationshipsmentioning
confidence: 99%
“…Studies have consistently reported impairment in sexual function in women with endometriosis that causes strain on intimate relationships. 45,62,70,72,75,79 In a multicenter Austrian and German study of 125 women with histologically confirmed endometriosis and dyspareunia, most women (78%) reported sexual distress, as measured on the Female Sexual Distress Scale, and 32% reported sexual dysfunction, as measured on the Female Sexual Function Index (FSFI). 74 Only 21% of women reported neither sexual distress nor sexual dysfunction.…”
Section: Personal Relationshipsmentioning
confidence: 99%
“…Over the last few years, several epidemiological studies have pointed out some relationship between cancer of the endometrium and BF and have shown that long periods of BF are associated with a reduced risk of this type of neoplasia. [42][43][44]…”
Section: Cancer Of the Endometriummentioning
confidence: 99%